กระบวนการเลิกใช้สารเสพติดก่อนเข้าสู่การเป็นสมาชิกกลุ่มที่เห็นต่าง ในพื้นที่ 3 จังหวัดชายแดนภาคใต้ และ 4 อำเภอจังหวัดสงขลา - รอดการทุกข์, ณัชฎาวรรณ; หงส์ชยางกูร, กุลทัต; สุธีรวุฒิ, พงค์เทพ (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 28 No 3 (2560): Academic Services Journal, Prince of Songkla UniversityDO - 10.14456/asj-psu.2017.50, 2017)
การวิจัยเชิงคุณภาพนี้มีวัตถุประสงค์ เพื่อศึกษากระบวนการเลิกใช้สารเสพติดก่อนเข้าสู่การเป็นสมาชิกกลุ่มที่เห็นต่างในพื้นที่ 3 จังหวัดชายแดนภาคใต้ และ 4 อำเภอจังหวัดสงขลา คัดเลือกกลุ่มตัวอย่างแบบเฉพาะเจาะจง โดยเป็นสมาชิกกลุ่มที่เห็นต่าง ระดับแกนนำและระดับปฏิบัติการที่เลิกสารเสพติดแล้วในปัจจุบันและสมัครใจให้ข้อมูล เครื่องมือวิจัยเป็นแบบสัมภาษณ์ข้อมูลทั่วไป และแนวคำถามการสัมภาษณ์แบบกึ่งมีโครงสร้างในการเลิกใช้สารเสพติดก่อนเข้าสู่การเป็นสมาชิกกลุ่มที่เห็นต่างในพื้นที่ 3 จังหวัดชายแดนภาคใต้ และ 4 อำเภอจังหวัดสงขลา ผ่านการตรวจสอบจากผู้ทรงคุณวุฒิจำนวน 3 ท่าน และผู้วิจัยมีประสบการณ์การเรียนวิชาวิจัยคุณภาพ และฝึกสัมภาษณ์นำร่อง 1 ราย ก่อนเก็บข้อมูลจริง เก็บข้อมูลโดยการสัมภาษณ์แบบเจาะลึกร่วมกับการสังเกต ระหว่างเดือนพฤศจิกายน พ.ศ. 2557-เดือนพฤศจิกายน พ.ศ. 2558 วิเคราะห์ข้อมูลเชิงคุณภาพโดยการวิเคราะห์เนื้อหา ผลการศึกษา กลุ่มตัวอย่างทั้งหมด 10 คน เป็นเพศชาย ส่วนใหญ่เป็นวัยกลางคน ทั้งหมดเรียนจบสายศาสนาชั้น 10 อาชีพหลักทำสวนยาง ระยะเวลาที่เป็นสมาชิกกลุ่มที่เห็นต่าง ตั้งแต่ 9-30 ปี และผลการศึกษากระบวนการเลิกใช้สารเสพติดมี 3 ประเด็น คือ 1) การสร้างอุดมการณ์เลิกใช้สารเสพติด โดยการเล่าเรื่องศาสนา การเล่าเรื่องบรรพบุรุษ และการเล่าการต่อสู้เพื่อบ้านเกิด 2) การสร้างร่างกายให้แข็งแรง โดยการฝึกฝนกระบวนท่า 12 ท่า และการออกกำลังกาย 3) การควบคุมการเลิกยา ด้วยการควบคุมตนเอง เพื่อนคุม องค์กรควบคุม และ สังคมควบคุม จากผลการศึกษาพบว่า กระบวนการเลิกใช้สารเสพติดในกลุ่มที่เห็นต่างมีจุดเด่นที่การสร้างอุดมการณ์ การสร้างร่างกายให้แข็งแรง และการควบคุมการเลิกใช้ยาจากกลุ่มสังคม องค์กร และเพื่อน ซึ่งแตกต่างไปจากการบำบัดที่มีใช้อยู่ในปัจจุบัน ผลการศึกษาทำให้เข้าใจประสบการณ์ในกระบวนการเลิกใช้สารเสพติดที่เกิดจากอุดมการณ์ที่แน่วแน่ที่ได้มาจากความศรัทธาในศาสนา ความภาคภูมิใจในบรรพบุรุษและการต่อสู้เพื่อบ้านเกิด รวมทั้งการควบคุมการเลิกยาที่ครอบคลุมทั้งจากตนเอง เพื่อน องค์กร และสังคม ซึ่งบุคลากรหรือองค์กรที่มีบทบาทหน้าที่ในการบำบัดรักษาผู้ใช้สารเสพติดสามารถนำไปประยุกต์ใช้ในกระบวนการบำบัดรักษาในปัจจุบัน คำสำคัญ: กระบวนการเลิกใช้สารเสพติด, กลุ่มที่เห็นต่าง, จังหวัดชายแดนภาคใต้   The objective of this qualitative research was to investigate the process of ending substance abuse before becoming members of a specific group in the three southern border provinces and the four districts of Songkhla Province. Samples of the study were selected using purposive sampling from members of a specific group in the study area. They were those who were leaders and those who were in the practical level who had stopped substance abuse and were willing to provide information. The research instruments were an interviewing form consisting of questions asking general data, and a semi-structured questions asking about ending substance abuse before becoming members of the specific group in the three southern border provinces and the four districts of Songkhla Province. The instruments were tested by three experts. The researcher, as an important instrument, had taken a course in qualitative research, and piloted an interview before the actual use for data collection. Data were collected through in-depth interviews and observation from November 2014 to November 2015. The qualitative data were analyzed using content analysis. The study found that all the ten informants were male, most of them were middle-aged, completed Grade 10 of the religious stream, with rubber plantations as the main occupation, had been members of the specific group ranging from 9 years to 30 years, and all of them had had used only one type of addictive substance that is marijuana. It was also found that there were three themes in the process of ending substance abuse: 1) Creating an ideology of ending substance abuse by telling about the religion, ancestors, and fighting for the homeland. 2) Building a healthy body by practicing 12 poses and exercising. 3) Controlling the ending of substance abuse by controlling themselves, being controlled by peers, by the organization and by society. Furthermore, The outstanding point of the process of ending substance abuse was that it was controlled by society, organization and peers which is different from therapies and treatments currently used. The study results provide understanding of experience in the process of ending substance abuse derived from ideology acquired from faith or belief in the religion, pride in ancestors who fought for the homeland, and self-control as well as control by peers, the organization and society. Personnel or organizations responsible for substance abuse treatment can apply the study results in the present treatment process. Keywords: process of ending substance abuse, group that thinks differently, southern border provinces